Assessment of Awareness of Risk Factors for Puerperal Psychosis among Pregnant Women Attending the Antenatal Unit at Abubakar Tafawa Balewa University Teaching Hospital, Bauchi - Musa, Muhammad Maryam; Maimuna, Muhammad; Rahayu, Lale Budi Hutami; Rahayu, Supiani (Balai Publikasi Indonesia, 2026)
Postpartum psychosis (PPP) is a severe mental health disorder characterized by the acute onset of psychotic symptoms such as delusions, hallucinations, and mood disturbances shortly after childbirth. Although it affects 1-2 per 1,000 women globally, its impact is particularly severe in low-resource settings like Nigeria, where cultural stigma, limited mental health infrastructure, and low awareness lead to under diagnosis and poor outcomes. This study aimed to assess the awareness of puerperal psychosis among pregnant women attending the Antenatal Care (ANC) unit at Abubakar Tafawa Balewa University Teaching Hospital (ATBUTH) in Bauchi, Nigeria. A descriptive survey design was employed, and data were collected from 129 respondents selected via simple random sampling, using a structured questionnaire. The results indicated that while a majority (71.32%) of respondents had heard of postpartum psychosis, there was a significant deficit in detailed knowledge. Only 56.53% could accurately define it as a severe mental disorder post-childbirth, and misconceptions about causes and symptoms were common. Key risk factors such as sleep deprivation, family history of bipolar disorder, and impaired mother-infant bonding were correctly identified by most. For prevention, respondents strongly endorsed educational programs, postnatal screening for high-risk women, frequent ANC visits, family support, and ensuring adequate rest. The study concludes that despite basic recognition of PPP, profound knowledge gaps persist among pregnant women in this setting. It underscores the urgent need for integrated, educational interventions during antenatal care and the routine inclusion of mental health screenings to facilitate early identification, management, and ultimately, improved maternal and infant outcomes in Northern Nigeria.